3D printing molecular sieve catalyst and preparation method and application thereof
By using ZSM-5 molecular sieve with core-shell structure in the 3D printed molecular sieve catalyst, the side reaction problem caused by high acidic site density in the existing technology is solved, and the effect of improving catalytic activity and optimizing product distribution is achieved.
Patent Information
- Application Number
- CN202311006409.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2023-07-31
- Filing Date
- 2023-08-10
- Publication Date
- 2025-02-14
- Estimated Expiration
- 2043-08-10
AI Technical Summary
The external surface of existing 3D printed molecular sieve catalysts has high acidic sites density, resulting in serious side reactions such as hydrogen transfer, which cannot meet application needs.
Using ZSM-5 molecular sieve with core-shell structure, the composition of carrier and molecular sieve is to reduce the occurrence of side reactions on the outer surface of the molecular sieve, increase the mesoporous volume, and shorten the reactant transport path, thereby optimizing product distribution.
It effectively reduces the side reactions on the outer surface of the molecular sieve, improves catalytic activity, optimizes product distribution, and is simple in preparation and has low equipment requirements.
Smart Images

Figure CN119425773A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the field of molecular sieve catalysts, and in particular to a 3D printed molecular sieve catalyst and a preparation method and application thereof. Background Art
[0002] The rapid growth of global chemical market demand has stimulated the vigorous development of catalytic cracking technology to increase the production of low-carbon olefins. In the 1970s, Mobil Corporation developed ZSM-5 molecular sieve, which has straight pores. and sinusoidal pores It has become the most competitive solid acid catalyst with its unique shape-selective catalytic effect and excellent thermal / hydrothermal stability. In practical applications, molecular sieve powder needs to be processed with binder / matrix materials into shaped catalysts such as microspheres, granules or strips before it can be used. The structure, composition and catalytic performance of the shaped catalyst will be very different from the initial molecular sieve powder. Therefore, how to optimize the catalyst molding method to improve the accessibility of the active sites of molecular sieve-based catalysts and improve the reaction performance is an important issue in the research and development and production of molecular sieve catalysts.
[0003] Processing solid powdered catalytic materials into structured catalysts with open pores (such as honeycomb ceramics) will effectively improve their mass transfer / heat transfer capabilities. 3D printing, also known as additive manufacturing, is based on a three-dimensional digital model file, and solidifies ink with a certain flow capacity by stacking layers to achieve material molding of complex geometric shapes. Compared with the traditional extrusion molding method, 3D printing molding technology has the advantages of high precision, multifunctional material integration and digital / flexible design. Up to now, a variety of 3D printed structured catalysts with molecular sieves as the main active components have shown great application potential in alkane catalytic cracking, ethylene oxidation, carbon monoxide oxidation, xylene isomerization and α-pinene isomerization reactions. For example, Stuecker et al. (Industrial & Engineering Chemistry Research, 2005, 44, 302) prepared alternating stacked structured catalysts by extrusion molding 3D printing, which can significantly improve the mass transfer efficiency of carbon monoxide catalytic oxidation reaction and keep the pressure drop loss at a low level. Currently, molecular sieves can be combined on the surface of 3D printed structured materials by secondary growth, surface deposition or coordination (X. Li, et al, Chemical Engineering Journal 2018, 333, 545; E. et.al, Applied Catalysis A: General 2019, 579, 75; CY Chaparro-Garnica, et.al, ACS Applied Materials & Interfaces 2020, 12, 54573; A. Lind et.al, Materials & Design 2020, 187, 108377; X. Li, ACS Applied Energy Materials 2018, 1, 2740). However, the catalyst surface obtained by the above method directly exposes the ZSM-5 molecular sieve, which has a high density of external surface acid sites, is prone to side reactions such as hydrogen transfer and aromatization, and aggravates the formation of surface carbon. In addition, the microstructure of the molecular sieve is not conducive to the rapid diffusion of products such as low-carbon olefins.
[0004] In summary, the density of acid sites on the outer surface of 3D printed molecular sieve catalysts obtained by existing methods is high, which easily induces side reactions such as hydrogen transfer and aromatization, aggravates the formation of surface carbon, and cannot meet application requirements. In view of this, the development of core-shell structured 3D printed catalysts with a weakly acidic passivation layer on the outer surface has application value. Summary of the invention
[0005] The purpose of the present invention is to overcome the problems of high density of acid sites on the outer surface and serious side reactions such as hydrogen transfer in the prepared 3D printed molecular sieve catalyst in the prior art, and to provide a 3D printed molecular sieve catalyst and a preparation method and application thereof. The 3D printed molecular sieve catalyst has a ZSM-5 molecular sieve with a core-shell structure distributed on the outer surface. The composition of the core-shell structure and the molecular sieve is conducive to reducing the occurrence of side reactions on the outer surface of the molecular sieve, increasing the mesopore volume, shortening the reactant transmission path, and thus optimizing the product distribution. The preparation method of the catalyst is simple and the synthesis process has low equipment requirements.
[0006] In order to achieve the above-mentioned object, the first aspect of the present invention provides a 3D printed molecular sieve catalyst, wherein the catalyst comprises a carrier and a ZSM-5 molecular sieve having a core-shell structure, and the mass percentage of the ZSM-5 molecular sieve in the catalyst is 20-45%;
[0007] The ZSM-5 molecular sieve comprises a core phase ZSM-5 molecular sieve and a shell ZSM-5 molecular sieve, wherein the core phase ZSM-5 molecular sieve is distributed on the outer surface of the carrier in the form of micron particle aggregates, and the average particle size of the micron particles is 1-5 microns;
[0008] The shell ZSM-5 molecular sieve covers the outer surface of the core phase ZSM-5 molecular sieve in the form of nanoparticles, and the average particle size of the nanoparticles is 50-300nm; the average thickness of the coating layer formed by the shell ZSM-5 molecular sieve is 50-400nm.
[0009] Preferably, the silicon to aluminum atomic molar ratio of the core phase ZSM-5 molecular sieve is 10-25, preferably 12-23.
[0010] Preferably, the molar ratio of silicon to aluminum atoms in the shell ZSM-5 molecular sieve is 30-100, preferably 40-85.
[0011] A second aspect of the present invention provides a method for preparing a 3D printed molecular sieve catalyst, characterized in that the method comprises the following steps:
[0012] (1) providing an aluminosilicate photosensitive resin slurry containing aluminosilicate and a photosensitive resin, and then performing 3D printing to obtain an aluminosilicate ceramic body;
[0013] (2) sintering the aluminosilicate ceramic body to obtain an aluminosilicate ceramic carrier;
[0014] (3) crystallizing a crystallization mother solution containing a silicon source, an aluminum source, a template, an alkali source and water to obtain a crystallization incubation solution;
[0015] (4) hydrothermally crystallizing the aluminosilicate ceramic carrier in a crystallization incubation solution, and then calcining a solid product obtained by the hydrothermal crystallization to obtain an intermediate product;
[0016] (5) The intermediate product is subjected to a desiliconization-recrystallization reaction in a composite alkali solution, and a 3D printed molecular sieve catalyst is obtained after calcination.
[0017] The third aspect of the present invention provides a 3D printed molecular sieve catalyst prepared by the preparation method described in the second aspect.
[0018] The fourth aspect of the present invention provides an application of the 3D printed molecular sieve catalyst described in the first aspect or the third aspect in a catalytic cracking reaction.
[0019] Through the above technical solution, the present invention has the following advantages:
[0020] (1) The 3D printed molecular sieve catalyst provided by the present invention comprises a ZSM-5 molecular sieve having a core-shell structure, wherein the shell ZSM-5 molecular sieve has a high silicon-aluminum ratio, and the core phase ZSM-5 molecular sieve has a low silicon-aluminum ratio. This structure and composition are conducive to reducing the side reactions on the outer surface of the molecular sieve, increasing the mesopore volume, shortening the reactant transport path, improving the accessibility of the active center and the utilization rate of the acidic site of the molecular sieve, thereby improving the catalytic activity of the molecular sieve catalyst;
[0021] (2) The preparation method provided by the present invention can establish a model through three-dimensional software, and can customize complex three-dimensional structures suitable for different scenes. It does not rely on molds, and does not require complex post-processing of the carrier. The three-dimensional channel structure of the carrier is simple and controllable;
[0022] (3) In the present invention, preferably, the prepared molecular sieve catalyst is easy to separate and recover from the synthesis solution, and the synthesis process has low requirements on equipment;
[0023] (4) In the present invention, preferably, the provided molecular sieve catalyst has high catalytic activity and the advantage of reducing bed pressure drop in the performance test of catalytic cracking reaction compared with traditional powder particle molecular sieve catalysts, and has application prospects in the field of catalytic cracking in the future. BRIEF DESCRIPTION OF THE DRAWINGS
[0024] Figure 1 is a cross-sectional view of the three-dimensional model test established in Example 1;
[0025] Figure 2 is a photo of the 3D printed molecular sieve catalyst prepared in Example 1;
[0026] Figure 3 is the XRD pattern of the 3D printed molecular sieve catalyst prepared in Example 1;
[0027] Figure 4 This is a scanning electron microscope image of the catalyst prepared in Example 1 before the growth of the shell layer ZSM-5 molecular sieve;
[0028] Figure 5 This is a scanning electron microscope image of the 3D printed molecular sieve catalyst obtained in Example 1 at a magnification of 50K times;
[0029] Figure 6 is a transmission electron microscopy image of the 3D printed molecular sieve catalyst prepared in Example 1;
[0030] Figure 7 is the isothermal adsorption curve of the 3D printed molecular sieve catalyst prepared in Example 1;
[0031] Figure 8 is the pore distribution curve of the 3D printed molecular sieve catalyst prepared in Example 1;
[0032] Fig. 9 is a scanning electron microscope image of the catalyst prepared in Comparative Example 1;
[0033] Fig.10 This is a scanning electron microscope image of the catalyst prepared in Comparative Example 2. DETAILED DESCRIPTION
[0034] The endpoints and any values of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values should be understood to include values close to these ranges or values. For numerical ranges, the endpoint values of each range, the endpoint values of each range and the individual point values, and the individual point values can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article.
[0035] The first aspect of the present invention provides a 3D printed molecular sieve catalyst, wherein the catalyst comprises a carrier and a ZSM-5 molecular sieve having a core-shell structure, and the mass percentage of the ZSM-5 molecular sieve in the catalyst is 20-45%;
[0036] The ZSM-5 molecular sieve comprises a core phase ZSM-5 molecular sieve and a shell ZSM-5 molecular sieve, wherein the core phase ZSM-5 molecular sieve is distributed on the outer surface of the carrier in the form of micron particle aggregates, and the average particle size of the micron particles is 1-5 microns;
[0037] The shell ZSM-5 molecular sieve covers the outer surface of the core phase ZSM-5 molecular sieve in the form of nanoparticles, and the average particle size of the nanoparticles is 50-300nm; the average thickness of the coating layer formed by the shell ZSM-5 molecular sieve is 50-400nm.
[0038] The 3D printed molecular sieve catalyst provided by the present invention comprises a ZSM-5 molecular sieve with a core-shell structure and a carrier, the carrier has good regularity, the molecular sieve mass percentage in the 3D molecular sieve catalyst is high, the structural precision is high, and the ZSM-5 molecular sieve is directly exposed to the outer surface of the carrier through in-situ growth, which has the advantage of high accessibility of the active center.
[0039] In the present invention, the core phase ZSM-5 molecular sieve refers to a micron-sized ZSM-5 molecular sieve grown on the outer surface of the carrier, such as Figure 4 As shown, the particle size of the core phase ZSM-5 molecular sieve is micrometer level. The shell ZSM-5 molecular sieve refers to a nano ZSM-5 molecular sieve grown on the outer surface of the core phase molecular sieve by desiliconization-recrystallization, and the particle size of the shell ZSM-5 molecular sieve is nanometer level. In the present invention, the core phase molecular sieve and the shell molecular sieve can be distinguished by transmission electron microscopy observation.
[0040] According to the present invention, preferably, the mass percentage of ZSM-5 molecular sieve in the catalyst is 30-43%. In the present invention, the mass percentage of molecular sieve in the molecular sieve catalyst is expressed by relative crystallinity, and is tested with commercial molecular sieve crystallinity of 100% with reference to ASTMD3906-03 standard method (Tianjin Nanhua Catalyst Co., Ltd., Na-type ZSM-5 molecular sieve of Nankai University Catalyst Factory, silicon-aluminum ratio 25). Test instrument: D5005 X-ray diffractometer of Siemens, Germany. Test conditions: Cu target, Kα radiation, solid detector, tube voltage 40kV, tube current 40mA, step scan, step width 0.02°, prefabrication time 2s, scanning range 5°-70°.
[0041] According to the present invention, preferably, the mass percentage of the carrier in the catalyst is 55-80%, preferably 57-70%. In the present invention, the mass percentage of the carrier in the catalyst is determined by grinding the whole catalyst and testing the crystallinity, and the crystallinity represents the mass percentage of the molecular sieve in the catalyst, and the mass percentage of the carrier = 100% - the mass percentage of the molecular sieve.
[0042] In the present invention, the composition of the carrier includes silicon dioxide and aluminum oxide, and the ratio of silicon dioxide to aluminum oxide in the carrier is not particularly limited. Preferably, the carrier is obtained by a 3D printing method, and the composition of the carrier satisfies the 3D printing conditions. The 3D printing process is described in detail in the preparation method section. In the process of forming a core-shell structure of the ZSM-5 molecular sieve on the surface of the carrier, crystallization and desiliconization-recrystallization reactions are carried out, so that the ratio of silicon dioxide to aluminum oxide in the carrier changes. Therefore, the composition of the carrier is not too limited.
[0043] In the present invention, the carrier is a carrier obtained by 3D printing, and the selection range of the specific structure of the carrier is relatively wide. Preferably, the carrier has a multi-pore self-supporting three-dimensional structure, and further preferably has a self-supporting three-dimensional structure with parallel radial and axial interconnected pore structures.
[0044] According to the present invention, preferably, in the core phase ZSM-5 molecular sieve, the average particle size of the micron particles is 1.5-4.5 microns. In the present invention, the average particle size of the core phase ZSM-5 molecular sieve micron particles is tested in an electron microscope (Hitachi scanning electron microscope, S-4800), and the average value obtained by randomly measuring the grain size of 20 molecular sieve micron particles is obtained by Nano Measurer software. In the measurement process, the size of a molecular sieve micron particle is the straight-line distance obtained by connecting the two farthest endpoints on the particle in the electron microscopic image.
[0045] According to the present invention, preferably, in the shell ZSM-5 molecular sieve, the average particle size of the nanoparticles is 70-280nm. In the present invention, the average particle size of the nanoparticles is tested in a transmission electron microscope, and the average value is obtained by randomly measuring the grain size of 20 molecular sieve nanoparticles through Nano Measurer software. In the measurement process, the size of a molecular sieve nanoparticle is the straight-line distance obtained by connecting the two farthest endpoints on the particle in the electron microscopic image.
[0046] According to the present invention, different morphologies of the core phase and the shell layer are observed by transmission electron microscopy, the core phase ZSM-5 molecular sieve presents a hexagonal prism stack with a smooth outer surface, and the shell ZSM-5 molecular sieve presents a rough and porous nano-grain aggregate. Preferably, the average thickness of the coating formed by the shell ZSM-5 molecular sieve is 100-300nm. The average thickness is the average value obtained by randomly measuring the shell thickness at 20 locations in the transmission electron microscope image.
[0047] According to the present invention, preferably, the silicon-aluminum atomic molar ratio of the core-phase ZSM-5 molecular sieve is 10-25, preferably 12-23. In the present invention, the silicon-aluminum atomic molar ratio of the core-phase ZSM-5 molecular sieve grown on the outer surface of the catalyst carrier is tested by XPS, and the silicon-aluminum atomic molar ratio of the core-phase ZSM-5 molecular sieve is the silicon-aluminum atomic molar ratio measured when the shell layer is not grown.
[0048] According to the present invention, preferably, the molar ratio of silicon to aluminum atoms in the shell ZSM-5 molecular sieve is 30-100, preferably 40-85. In the present invention, the surface chemical composition of the catalyst can be tested by XPS, and the surface Si / Al ratio can be calculated by XPS signal to obtain the silicon and aluminum content of the outermost shell ZSM-5 molecular sieve of the catalyst.
[0049] In the present invention, the molar ratio of silicon to aluminum atoms is the molar ratio of Si / Al.
[0050] In the present invention, preferably, the shell ZSM-5 molecular sieve of the 3D molecular sieve catalyst has a high silicon-aluminum ratio, and the core phase ZSM-5 has a low silicon-aluminum ratio, which has the advantages of reducing side reactions on the outer surface of the molecular sieve, increasing the mesopore volume, shortening the reactant transport path, and improving the accessibility of the active center and the utilization rate of the acidic site of the molecular sieve.
[0051] According to the present invention, preferably, the catalyst has micropores and mesopores. In the present invention, the catalyst has a multi-level pore structure of mesopores and micropores, which is beneficial to improving the catalytic activity of the catalyst.
[0052] According to the present invention, preferably, the micropore volume of the catalyst is 0.03-0.08 cm 3 / g, preferably 0.04-0.07cm 3 / g.
[0053] According to the present invention, preferably, the mesopore volume of the catalyst is 0.08-0.15 cm 3 / g, preferably 0.1-0.13cm 3 / g.
[0054] In the present invention, the micropore volume and mesopore volume of the molecular sieve catalyst are measured by low temperature nitrogen adsorption capacity method, and the test instrument is ASAP2400 static nitrogen adsorption instrument of Micromeritics. Test conditions: the sample is vacuum degassed for 4 hours at 1.33Pa and 300°C, and then contacted with liquid nitrogen at 77K, isothermally adsorbed and desorbed, adsorption and desorption isotherms are measured, and the micropore volume and mesopore volume are calculated using the BET formula.
[0055] A second aspect of the present invention provides a method for preparing a 3D printed molecular sieve catalyst, wherein the method comprises the following steps:
[0056] (1) providing an aluminosilicate photosensitive resin slurry containing aluminosilicate and a photosensitive resin, and then performing 3D printing to obtain an aluminosilicate ceramic body;
[0057] (2) sintering the aluminosilicate ceramic body to obtain an aluminosilicate ceramic carrier;
[0058] (3) crystallizing a crystallization mother solution containing a silicon source, an aluminum source, a template, an alkali source and water to obtain a crystallization incubation solution;
[0059] (4) hydrothermally crystallizing the aluminosilicate ceramic carrier in a crystallization incubation solution, and then calcining a solid product obtained by the hydrothermal crystallization to obtain an intermediate product;
[0060] (5) The intermediate product is subjected to a desiliconization-recrystallization reaction in a composite alkali solution, and a 3D printed molecular sieve catalyst is obtained after calcination.
[0061] In the present invention, the aluminosilicate ceramic carrier is hydrothermally crystallized in a crystallization incubation solution, and a molecular sieve with good dispersibility and high catalytic activity can be obtained on the aluminosilicate ceramic carrier. The preparation process is simple and can form a complex three-dimensional structure without relying on a mold. The prepared molecular sieve catalyst has high structural accuracy, high molecular sieve content in the catalyst, and high catalytic activity.
[0062] In the present invention, preferably, the aluminosilicate photosensitive resin slurry in step (1) can be obtained by mixing aluminosilicate and photosensitive resin. There is no particular limitation on the mixing method. According to a preferred embodiment of the present invention, the mixing can be achieved by ball milling, the ball milling speed is 250-500 rpm, preferably 280-450 rpm, and the ball milling time is 3-18 hours, preferably 5-15 hours.
[0063] According to the present invention, preferably, the aluminosilicate comprises silicon-based powder and auxiliary powder, the mass percentage of silicon-based powder on a dry basis is 35-65%, preferably 45-60%, and the mass percentage of auxiliary powder on a dry basis is 35-65%, preferably 40-55%. The use of such aluminosilicate with such a preferred composition is more conducive to the carrier material obtained after sintering taking into account both structural stability and chemical activity under hydrothermal conditions.
[0064] In the present invention, the aluminosilicate has the conventional meaning in the art. Aluminosilicate is a class of substances including commonly used mineral soils, the main components of which are aluminum oxide and silicon dioxide. The molecular formula can be expressed as xAl2O3·ySiO2, wherein the ratio of aluminum oxide to silicon dioxide is not constant.
[0065] In the present invention, there is no particular limitation on the particle size of the aluminosilicate, which can be larger particles or smaller powders, as long as the aluminosilicate is evenly distributed in the carrier. If larger particles are used, it is preferred to further improve their uniformity through subsequent ball milling. Preferably, the particle size D90 of the aluminosilicate is in the range of 0.5-100 μm.
[0066] In the present invention, preferably, the above-mentioned silicon-based powder is mixed with an auxiliary powder to obtain aluminosilicate, and the silicon-based powder can be used as a silicon source for growing molecular sieves on a carrier in the subsequent preparation process. When the amount of the silicon-based powder added is too much, the silicon dissolution degree of the carrier after calcination during the hydrothermal crystallization process is too high, and the in-situ molecular sieve growth reaction rate on the carrier surface is too high, making the carrier structure unstable and collapsing, and no longer maintaining the original self-supporting structure. When the amount of silicon-based powder added is insufficient, the silicon dissolution of the carrier after calcination during the hydrothermal crystallization process is limited, resulting in a too low in-situ molecular sieve growth reaction rate on the carrier surface, so that the molecular sieve content in the catalyst finally obtained is low, and the catalytic reaction requirements cannot be met.
[0067] In the present invention, there is no particular limitation on the particle sizes of the silicon-based powder and the auxiliary powder. It is preferred that the particle size of the aluminosilicate obtained after mixing meets the above-mentioned particle size requirements.
[0068] According to the present invention, the silicon-based powder may be conventional silicon-based powder in the art, and those skilled in the art can make an adaptive selection according to needs. Preferably, the silicon-based powder is selected from at least one of silicon dioxide, white carbon black and diatomaceous earth.
[0069] According to the present invention, there is no particular limitation on the auxiliary powder, as long as it is chemically inert under hydrothermal conditions to maintain the stability of the self-supporting structure. Preferably, the auxiliary powder is selected from at least one of kaolin, metakaolin, bentonite and montmorillonite.
[0070] According to the present invention, the amount of the aluminosilicate and the photosensitive resin can be selected in a relatively wide range, so as to ensure that the 3D printing process proceeds smoothly. Preferably, the mass ratio of the aluminosilicate to the photosensitive resin is 0.5-1:1, such as 0.5:1, 0.6:1, 0.7:1, 0.8:1, 0.9:1, 1:1, and any range between any two values, preferably 0.6-0.9:1.
[0071] According to the present invention, the specific composition of the photosensitive resin has a wide range of selections and can be selected according to conventional technical means in the art. Preferably, the raw materials of the photosensitive resin include 1-5% of photoinitiator, 30-65% of prepolymer, and 30-65% of monomer by mass percentage, preferably including 1.5-4% of photoinitiator, 35-60% of prepolymer, and 37-62% of monomer by mass percentage. The photosensitive resin composed of the above raw materials is used for 3D printing, which has fast curing speed and high production efficiency.
[0072] In the present invention, the photoinitiator can be a conventional photoinitiator in the art. Preferably, the photoinitiator is selected from at least one of 2,4,6-trimethylbenzoyl-diphenylphosphine oxide (photoinitiator TPO), phenyl bis(2,4,6-trimethylbenzoyl)phosphine oxide (photoinitiator 819) and isopropylthioxanthone (ITX).
[0073] In the present invention, the prepolymer may be a conventional acrylate prepolymer in the art. Preferably, the prepolymer is an epoxy acrylate prepolymer and / or a polyurethane acrylate prepolymer.
[0074] In the present invention, the monomer may be a conventional monomer in the art. Preferably, the monomer is selected from at least one of 1,6-hexanediol diacrylate (HDDA), tripropylene glycol diacrylate (TPGDA) and trimethylolpropane triacrylate (TMPTA).
[0075] In the present invention, a 3D printing method is used to prepare an aluminosilicate ceramic body, a modeling software is used to perform a three-dimensional structure design, and an aluminosilicate photosensitive resin slurry is poured into a DLP light-curing printer material cylinder for printing to obtain an aluminosilicate ceramic body. In the present invention, "aluminosilicate ceramic body" is a general term for the prepared bodies, and the printing method can be used to customize complex three-dimensional structures suitable for different scenes, without relying on molds, and does not require complex post-processing of the carrier, and the three-dimensional channel structure of the carrier is simple and controllable.
[0076] In the present invention, preferably, a modeling software is used for three-dimensional structure design, and the modeling software is selected from SolidWorks, 3DMAX, AutoCAD or Materialise Magics.
[0077] According to the present invention, preferably, the conditions for 3D printing include: the light curing exposure power is 0.5-5mW / cm 2 The exposure time of the first layer is 15-30s, the exposure time of other layers is 5-15s, and the thickness of a single layer of photocuring is 20-100μm.
[0078] In the present invention, preferably, the obtained aluminosilicate ceramic body is also cleaned after printing. There is no particular limitation on the cleaning conditions, and those skilled in the art can make appropriate selections. According to a preferred embodiment of the present invention, anhydrous ethanol is used for sufficient cleaning.
[0079] The present invention does not particularly limit the size and structural shape of the aluminosilicate ceramic body, and those skilled in the art can make appropriate selections according to the specific application scenarios of the prepared catalyst. The present invention subsequently provides a specific preferred embodiment for use in a catalytic cracking catalyst, but the present invention is not limited thereto.
[0080] In the present invention, the aluminosilicate ceramic body provides a skeleton for the molecular sieve catalyst. The body has a multi-porous structure and forms an aluminosilicate ceramic carrier after sintering, so that the molecular sieve seeds in the crystallization incubation solution can grow rapidly on the carrier, thereby increasing the mass percentage of the molecular sieve (preferably ZSM-5) in the prepared molecular sieve catalyst.
[0081] According to the present invention, preferably, the aluminosilicate ceramic carrier has a multi-porous self-supporting three-dimensional structure. The present invention has no special limitation on the multi-porous self-supporting three-dimensional structure, which has the conventional interpretation in the art. Specifically, the "self-supporting" means that the aluminosilicate ceramic carrier has its own strength and rigidity, and can maintain its shape and stability without external support. The "multi-porous" means that the main frame of the aluminosilicate ceramic carrier has a multi-porous structure. There is no special limitation on the distribution of the pores, and it can be appropriately selected according to the specific catalyst application scenario. The distribution of the pores can be uniform, symmetrical, or uneven and asymmetrical. In order to further improve the application effect of the catalyst in catalytic cracking reactions, it is further preferred that the aluminosilicate ceramic carrier is a self-supporting three-dimensional structure with parallel radial and axial interconnected pore structures. The specific pore structure is as follows Figure 1 and Figure 2 shown.
[0082] According to the present invention, preferably, the method also includes pyrolyzing the aluminosilicate ceramic body before sintering to remove organic matter in the body, and the pyrolysis conditions include: temperature of 350-550°C and time of 5-15h; preferably, the pyrolysis conditions include: temperature of 380-520°C and time of 6-13h.
[0083] In the present invention, those skilled in the art can adjust the heating rate of the pyrolysis process as needed. Preferably, the heating rate of the pyrolysis process is 0.1-5°C / min, preferably 0.5-2°C / min.
[0084] According to the present invention, preferably, the sintering conditions in step (2) include: a temperature of 1100-1300° C. and a time of 5-20 hours. Further preferably, the sintering conditions in step (2) include: a temperature of 1150-1250° C. and a time of 8-16 hours.
[0085] In the present invention, the aluminosilicate ceramic body is sintered in step (2), and those skilled in the art can adjust the heating rate of the sintering process as needed. Preferably, the heating rate is 0.1-10°C / min, preferably 0.5-5°C / min.
[0086] According to the present invention, preferably, in the crystallization mother solution, the aluminum source is calculated as Al2O3, the silicon source is calculated as SiO2, the alkali source is calculated as alkali metal oxide X2O, and the molar ratio of SiO2:Al2O3:template:X2O:H2O is 1:(0.018-0.027):(0.18-0.27):(0.22-0.33):(65-100), preferably 1:(0.02-0.025):(0.2-0.25):(0.24-0.31):(70-90).
[0087] In the present invention, preferably, the silicon source, aluminum source and template are used to provide molecular sieve seeds for the crystallization mother solution, which helps to accelerate the growth rate of the molecular sieve on the aluminosilicate ceramic carrier and shorten the crystallization time of the molecular sieve.
[0088] According to the present invention, preferably, the silicon source may be a conventional silicon source in the art, and those skilled in the art may make an adaptive selection according to needs, preferably silica sol and / or tetraethyl orthosilicate.
[0089] According to the present invention, preferably, the aluminum source can be a conventional aluminum source in the art, and those skilled in the art can make an adaptive selection as needed, preferably selected from at least one of aluminum sulfate, aluminum isopropoxide and aluminum trichloride.
[0090] In the present invention, the template agent has a wide selection range and can be adaptively selected according to the specific type of molecular sieve to be synthesized. Preferably, the template agent is an organic amine microporous template agent known to those skilled in the art that can be used to prepare ZSM-5, preferably tetrapropylammonium hydroxide and / or tetrapropylammonium bromide.
[0091] In the present invention, the alkali source is a conventional alkali source in the art, and those skilled in the art can make an adaptive selection according to needs, preferably sodium hydroxide and / or potassium hydroxide.
[0092] In the present invention, the crystallization mother liquor is alkaline, and the pH value of the crystallization mother liquor is 9-12, preferably 10-11. When the pH value of the crystallization mother liquor is less than 9, an alkali source needs to be added to make the pH value of the crystallization mother liquor meet 9-12. Placing the carrier in the crystallization mother liquor in the above pH range for crystallization reaction can improve the solubility of the silicon aluminum raw material, shorten the induction period, and increase the crystallization speed.
[0093] According to the present invention, preferably, the crystallization conditions in step (3) include: a crystallization temperature of 155-185° C., preferably 165-180° C., and a crystallization time of 3-10 h, preferably 4-9 h.
[0094] In the present invention, the reaction equipment for the crystallization and hydrothermal crystallization has a wide range of options, and those skilled in the art can make adaptive choices as needed, preferably in a crystallization kettle. In the present invention, it is preferred that after the crystallization and / or hydrothermal crystallization is completed, the crystallization kettle is cooled (preferably to room temperature) and then opened. This preferred embodiment avoids the safety hazard when the kettle is opened due to the self-generated pressure in the kettle caused by the crystallization reaction at high temperature.
[0095] In the present invention, preferably, the crystallization mother liquor is crystallized under the above conditions to obtain a crystallization incubation solution, which can further improve the crystallinity of the prepared molecular sieve catalyst. The crystallization incubation solution contains molecular sieve seeds. From the perspective of crystal growth kinetics, the use of the incubation solution can significantly shorten the crystal nucleation period (nucleation period) on the carrier surface, thereby accelerating the molecular sieve crystallization process on the carrier surface.
[0096] According to the present invention, preferably, in step (4), the mass ratio of the aluminosilicate ceramic carrier to the crystallization incubation solution is 1:5-12, such as 1:5, 1:6, 1:7, 1:8, 1:9, 1:10, 1:11, 1:12, and any range between any two values, preferably 1:6.5-10. This preferred embodiment is more conducive to matching the dissolution rate of the silicon species of the carrier itself and the crystallization rate of the surface molecular sieve, and obtaining a crystallized product that takes into account both crystallinity and self-supporting structural strength.
[0097] According to the present invention, preferably, the conditions for the hydrothermal crystallization include: a crystallization temperature of 155-185° C., preferably 165-180° C., and a crystallization time of 12-40 h, preferably 15-35 h.
[0098] In the present invention, preferably, the method further comprises: post-processing the solid product obtained by hydrothermal crystallization, wherein the post-processing comprises washing and drying. The washing may be performed by conventional methods and conditions in the art, and according to some preferred embodiments of the present invention, the washing may be performed by deionized water.
[0099] In the present invention, drying can be carried out by conventional methods and conditions in the art. According to some preferred embodiments of the present invention, drying can be carried out in an oven under the conditions of: drying at 60-120° C. for 2-10 hours.
[0100] According to the present invention, there is no particular limitation on the conditions for the calcination, as long as the template in the solid product can be removed. Preferably, the calcination conditions include: a temperature of 500-600°C and a time of 4-8 hours. There is no particular limitation on the calcination equipment. Preferably, the calcination can be carried out in a muffle furnace.
[0101] According to the present invention, preferably, in step (5), the composite alkali solution includes alkali metal hydroxide and microporous template agent. The composite alkali solution is prepared by dissolving alkali metal hydroxide and microporous template agent in water. The desiliconization-recrystallization reaction is carried out using the composite alkali solution to form a ZSM-5 molecular sieve with a core-shell structure on the surface of the carrier.
[0102] In the present invention, the alkali metal hydroxide is an alkali metal hydroxide known to those skilled in the art and can be used to prepare ZSM-5, preferably sodium hydroxide and / or potassium hydroxide.
[0103] In the present invention, the microporous template agent is an organic amine microporous template agent known to those skilled in the art and can be used to prepare ZSM-5, and preferably can be tetrapropylammonium hydroxide and / or tetrapropylammonium bromide.
[0104] According to the present invention, preferably, the molar concentration of the alkali metal in the composite alkali solution in step (5) is 0.3-0.5 mol / L, preferably 0.34-0.46 mol / L; the molar concentration of the microporous template agent is 0.4-0.6 mol / L, preferably 0.44-0.56 mol / L.
[0105] In the present invention, preferably, a composite alkali solution having the above concentration ratio is used for desiliconization-recrystallization reaction, and a ZSM-5 molecular sieve having a specific core-shell structure can be formed on the surface of the carrier. If the molar concentration of the alkali metal is too high, the degree of desiliconization is too high, and the microporous structure of the molecular sieve is seriously damaged. If the molar concentration is too low, the degree of desiliconization is too low, and sufficient silicon source species cannot be provided for subsequent recrystallization, and the shell structure cannot be obtained; if the molar concentration of the microporous template agent is too high, it will be difficult for the shell ZSM-5 molecular sieve to form a porous structure, and the cost will increase. If the molar concentration of the microporous template agent is too low, the recrystallization rate is too low, and it is not easy to obtain a complete shell structure.
[0106] According to the present invention, preferably, in step (5), the mass ratio of the intermediate product to the composite alkali solution is 1:3-8, preferably 1:4-7, based on their respective total mass. The intermediate product and the composite alkali solution are subjected to a desiliconization-recrystallization reaction at the above mass ratio, and the silicon in the core phase ZSM-5 molecular sieve can be quickly removed, and a shell ZSM-5 molecular sieve coating layer of nanoparticles grows on the surface of the core phase ZSM-5 molecular sieve.
[0107] According to the present invention, preferably, the desiliconization-recrystallization conditions include: a crystallization temperature of 155-185° C., preferably 165-180° C., and a crystallization time of 15-50 hours, preferably 20-40 hours. Carrying out the desiliconization-recrystallization reaction under the above conditions is conducive to the formation of a stable ZSM-5 molecular sieve with a multi-level porous core-shell structure on the carrier surface, thereby improving the catalytic activity of the catalyst.
[0108] In the present invention, preferably, the method further comprises: post-processing the solid product obtained by desiliconization-recrystallization, and the post-processing comprises washing and drying. The washing can be carried out by conventional methods and conditions in the art. According to some preferred embodiments of the present invention, the washing can be carried out by deionized water.
[0109] In the present invention, drying can be carried out by conventional methods and conditions in the art. According to some preferred embodiments of the present invention, drying can be carried out in an oven under the conditions of: drying at 60-120° C. for 2-10 hours.
[0110] In the present invention, there is no particular limitation on the conditions for the calcination, as long as the template in the solid product can be removed. Preferably, the conditions for the calcination include: a temperature of 500-600°C and a time of 4-8 hours. There is no particular limitation on the calcination equipment, and preferably, the calcination can be carried out in a muffle furnace.
[0111] The third aspect of the present invention provides a 3D printed molecular sieve catalyst prepared by the preparation method described in the second aspect.
[0112] The fourth aspect of the present invention provides an application of the 3D printed molecular sieve catalyst described in the first aspect or the third aspect in a catalytic cracking reaction.
[0113] In the present invention, preferably, before using the 3D printed molecular sieve catalyst for catalytic cracking reaction, it is pretreated, preferably specifically including: exchanging the 3D printed molecular sieve catalyst with ammonia to obtain an ammonia-type catalyst, and then washing, drying and calcining the ammonia-type catalyst to obtain a hydrogen-type catalyst for catalytic cracking experiment. For the above pretreatment conditions, those skilled in the art can make adaptive selections and adjustments as needed.
[0114] In the present invention, preferably, the reaction conditions of the catalytic cracking reaction are: reaction pressure of 0.09-0.3 MPa, reaction temperature of 550-680°C, raw material feed weight space velocity of 50-100h -1 .
[0115] In the present invention, there is no particular limitation on the reaction device for the catalytic cracking reaction, and those skilled in the art can make an appropriate selection according to the application scenario of the molecular sieve catalyst. According to a preferred embodiment of the present invention, the catalytic cracking reaction can be carried out in a fixed bed reactor.
[0116] In the present invention, the prepared molecular sieve catalyst has high catalytic activity and has the advantage of reducing bed pressure drop, and can be widely used in catalytic cracking reactions.
[0117] According to a particularly preferred embodiment of the present invention, a method for preparing a 3D printed molecular sieve catalyst comprises the following steps:
[0118] (1) providing an aluminosilicate photosensitive resin slurry containing aluminosilicate and a photosensitive resin, and then performing 3D printing to obtain an aluminosilicate ceramic body;
[0119] (2) sintering the aluminosilicate ceramic body to obtain an aluminosilicate ceramic carrier;
[0120] (3) crystallizing a crystallization mother solution containing a silicon source, an aluminum source, a template, an alkali source and water, wherein the aluminum source is calculated as Al2O3, the silicon source is calculated as SiO2, the alkali source is calculated as X2O, and the molar ratio of SiO2:Al2O3:template:X2O:H2O is 1:(0.02-0.025):(0.2-0.25):(0.24-0.31):(70-90), and the crystallization conditions include: a crystallization temperature of 165-180°C and a crystallization time of 4-9h; obtaining a crystallization incubation solution;
[0121] (4) hydrothermally crystallizing the aluminosilicate ceramic carrier in a crystallization incubation solution, and then calcining a solid product obtained by the hydrothermal crystallization to obtain an intermediate product;
[0122] (5) subjecting the intermediate product to a desiliconization-recrystallization reaction in a composite alkali solution, wherein the mass ratio of the intermediate product to the composite alkali solution is 1:4-7 based on the total mass of each, and the desiliconization-recrystallization reaction is completed, and a 3D printed molecular sieve catalyst is obtained after calcination;
[0123] The composite alkali solution includes alkali metal hydroxide and a microporous template agent, wherein the alkali metal hydroxide is sodium hydroxide and / or potassium hydroxide, and the molar concentration of the alkali metal is 0.34-0.46 mol / L; the microporous template agent is tetrapropylammonium hydroxide and / or tetrapropylammonium bromide, and the molar concentration of the microporous template agent is 0.44-0.56 mol / L.
[0124] The present invention will be described in detail below through examples and comparative examples. In the following examples and comparative examples, unless otherwise specified, the reagents and materials used can be obtained commercially, and the room temperature is 25°C;
[0125] The ball milling was carried out using a Juchuang environmental protection vertical planetary ball mill (model JC-QM-0.4);
[0126] The three-dimensional model is established by Solidworks software;
[0127] The 3D printing is completed by a sinking DLP-3D printer (model SU136A or SU-100A) of Foshan Guanglei Intelligent Manufacturing Co., Ltd. (light source wavelength: 405nm);
[0128] The test methods and test conditions for the properties of the molecular sieve catalyst, such as the mass percentage of the molecular sieve, the surface morphology, the average particle size and the pore structure, are described in the aforementioned specification and will not be repeated here.
[0129] Example 1
[0130] (1) Preparation of aluminosilicate ceramic green body:
[0131] (1-1) Using diatomite as a silicon-based powder and metakaolin as an auxiliary powder, the silicon-based powder mass fraction is 60% (on a dry basis) and the auxiliary powder mass fraction is 40% (on a dry basis) to obtain aluminosilicate, wherein the D90 particle size of the aluminosilicate is 5.8 μm;
[0132] (1-2) 2,4,6-trimethylbenzoyl-diphenylphosphine oxide (TPO) is used as a photoinitiator, polyurethane acrylate prepolymer is used as a prepolymer, and 1,6-hexanediol diacrylate (HDDA) is used as a monomer, and the mixture is mixed according to the ratio of 4% of the photoinitiator, 35% of the prepolymer, and 61% of the monomer to obtain a photosensitive resin;
[0133] (1-3) mixing aluminosilicate and photosensitive resin in a mass ratio of 0.65:1, and fully ball milling in a ball mill for 14 hours (rotation speed 280 rpm) to obtain aluminosilicate photosensitive resin slurry;
[0134] (1-4) Perform three-dimensional structure design, import the three-dimensional model file into the 3D printing equipment, pour the aluminosilicate photosensitive resin slurry into the DLP light-curing printer material tank for printing, and the printing parameters are: exposure power 1mW / cm 2 , exposure time 10s (first layer exposure time 20s); after printing, the obtained aluminosilicate ceramic body is placed in anhydrous ethanol for thorough cleaning.
[0135] (2) drying the formed aluminosilicate ceramic body, and pyrolyzing and sintering the body. The specific pyrolysis and sintering conditions are: heating from room temperature to 450°C at a rate of 0.5°C / min, and maintaining for 8 hours; heating from 450°C to 1200°C at a rate of 3°C / min, and maintaining for 15 hours, to obtain an aluminosilicate ceramic carrier. The aluminosilicate ceramic carrier has Figure 1 A similar multi-porous self-supporting three-dimensional structure is a cylinder composed of strips arranged in a staggered manner horizontally and vertically, with a cross-sectional diameter of 1.27 cm and a height of 1.18 cm. The spacing between different strips on the same horizontal plane is 0.06 cm.
[0136] (3) Using silica sol (40wt% SiO2, Grace Ludox AS40) and aluminum sulfate (99wt%, Innochem) as the silicon source and aluminum source, respectively, and tetrapropylammonium hydroxide (TPAOH, 25wt%, Innochem) as the template, the silicon source, aluminum source, template and sodium hydroxide are added into water and mixed to obtain a crystallization mother solution, wherein the molar ratio of each raw material, i.e., SiO2:Al2O3:template:X2O:H2O, is 1:0.022:0.22:0.28:81. The above mixture is crystallized at 170°C for 6 hours to obtain a crystallization incubation solution.
[0137] (4) placing the aluminosilicate ceramic carrier in a crystallization incubation solution, wherein the mass ratio of the carrier to the crystallization incubation solution is 1:7.5, and hydrothermally crystallizing the carrier and the incubation solution mixture at 165° C. for 35 hours. After the hydrothermal crystallization is completed, the hydrothermal crystallization product is cooled, separated, washed, dried at 100° C. for 4 hours, and calcined at 550° C. for 4 hours to obtain an intermediate product.
[0138] (5) Sodium hydroxide and tetrapropylammonium hydroxide are dissolved in water and mixed to obtain a composite alkali solution, wherein the molar concentration of sodium hydroxide is 0.4 mol / L, and the molar concentration of tetrapropylammonium hydroxide is 0.5 mol / L. The intermediate product is placed in the composite alkali solution, wherein the mass ratio of the intermediate product to the composite alkali solution is 1:5, and a desiliconization-recrystallization reaction is carried out in a hydrothermal reactor at 170°C for 24 hours. After the reaction, the product is cooled, separated, washed, dried at 100°C for 4 hours, and calcined at 550°C for 4 hours to obtain a 3D printed molecular sieve catalyst.
[0139] Figure 1 This is a test cross-sectional diagram of the three-dimensional model established in Example 1. The three-dimensional structure design is performed by modeling software, and the structural shape of the molecular sieve catalyst can be selected according to actual needs. Figure 2 This is a photo of the 3D printed molecular sieve catalyst prepared in Example 1. The molecular sieve catalyst obtained by 3D printing realizes high-precision, digital design of the molecular sieve catalyst and has better regularity.
[0140] The XRD spectrum of the catalyst prepared in Example 1 is as follows: Figure 3 As shown, from Figure 3 It can be seen that the synthesized 3D printed molecular sieve catalyst has the characteristic diffraction peaks of ZSM-5 molecular sieve, and an obvious five-finger diffraction peak appears at 22.0-25.0° 2θ, and the mass percentage of ZSM-5 is 36%.
[0141] Figure 4 This is a scanning electron microscope image of the catalyst prepared in Example 1 before the shell ZSM-5 molecular sieve is grown. It can be seen from the figure that the core phase molecular sieve grows on the outermost surface of the catalyst and exists in the form of micron particle aggregates. The grain sizes of 20 molecular sieve micron particles are randomly measured, and the average particle size is calculated to be 3.5 microns.
[0142] Figure 5 This is a scanning electron microscope image of the 3D printed molecular sieve catalyst obtained in Example 1 at a magnification of 50K times, and Figure 4 By comparison, the growth of the shell ZSM-5 molecular sieve can be clearly seen.
[0143] Figure 6 This is a transmission electron microscope image of the 3D printed molecular sieve catalyst prepared in Example 1. Shell ZSM-5 molecular sieve and core ZSM-5 molecular sieve with different morphologies can be observed. The shell ZSM-5 molecular sieve is distributed on the outer surface of the core ZSM-5 molecular sieve and exists in the form of nanoparticle aggregates. The grain sizes of 20 molecular sieve nanoparticles were randomly measured, and the average particle size was 90nm. The average thickness of the coating layer formed by the shell ZSM-5 molecular sieve was 200nm. Figure 6The right side is an enlarged view of the square area circled on the left side. By zooming in, the unique lattice stripes of ZSM-5 molecular sieve can be observed, and it can be seen that the shell is formed by ZSM-5 molecular sieve.
[0144] Figure 7 is the isothermal adsorption curve of the 3D printed molecular sieve catalyst prepared in Example 1, Figure 8 is the pore distribution curve of the 3D printed molecular sieve catalyst prepared in Example 1, such as Figure 7 , Figure 8 As shown in Figure 2, a hysteresis loop can be observed in the adsorption isotherm of the 3D printed molecular sieve catalyst, and the presence of mesopores in the sample can be observed from the pore size distribution curve, with the micropore volume being 0.05 cm 3 / g, and the mesopore volume is 0.12cm 3 / g.
[0145] Example 2
[0146] (1) Preparation of aluminosilicate ceramic green body:
[0147] (1-1) Using diatomite as a silicon-based powder and metakaolin as an auxiliary powder, the silicon-based powder is mixed at a mass fraction of 60% (on a dry basis) and the auxiliary powder is mixed at a mass fraction of 40% (on a dry basis) to obtain aluminosilicate, wherein the D90 particle size of the aluminosilicate is 5 μm;
[0148] (1-2) 2,4,6-trimethylbenzoyl-diphenylphosphine oxide (TPO) is used as a photoinitiator, polyurethane acrylate prepolymer is used as a prepolymer, and 1,6-hexanediol diacrylate (HDDA) is used as a monomer, and the mixture is mixed according to the ratio of 4% of the photoinitiator, 35% of the prepolymer, and 61% of the monomer to obtain a photosensitive resin;
[0149] (1-3) mixing aluminosilicate and photosensitive resin in a mass ratio of 0.65:1, and fully ball milling in a ball mill for 14 hours (rotation speed 280 rpm) to obtain aluminosilicate photosensitive resin slurry;
[0150] (1-4) Perform 3D structure design, import the 3D model file into the 3D printing device, perform 3D printing according to the 3D model of Example 1, pour the aluminosilicate photosensitive resin slurry into the DLP light-curing printer material tank for printing, and the printing parameters are: exposure power 1mW / cm 2 , exposure time 10s (first layer exposure time 20s); after printing, the obtained aluminosilicate ceramic body is placed in anhydrous ethanol for thorough cleaning.
[0151] (2) The formed aluminosilicate ceramic body is dried, pyrolyzed and sintered. The specific pyrolysis and sintering conditions are: heating from room temperature to 450°C at a heating rate of 0.5°C / min and maintaining for 8 hours; heating from 450°C to 1200°C at a heating rate of 3°C / min and maintaining for 15 hours to obtain an aluminosilicate ceramic carrier.
[0152] (3) Using silica sol (40wt% SiO2, Qingdao Junqiang New Materials Co., Ltd.) and aluminum sulfate (99wt%, Innochem) as the silicon source and aluminum source, respectively, and tetrapropylammonium hydroxide (TPAOH, 25wt%, Innochem) as the template, the silicon source, aluminum source, template and sodium hydroxide are added into water and mixed to obtain a crystallization mother solution, wherein the molar ratio of each raw material, i.e., SiO2:Al2O3:template:X2O:H2O, is 1:0.021:0.21:0.26:74. The above mixture is crystallized at 165°C for 9 hours to obtain a crystallization incubation solution.
[0153] (4) placing the aluminosilicate ceramic carrier in a crystallization incubation solution, wherein the mass ratio of the carrier to the crystallization incubation solution is 1:6.8, and hydrothermally crystallizing the carrier and the incubation solution mixture at 170° C. for 32 hours. After the hydrothermal crystallization is completed, the hydrothermal crystallization product is cooled, separated, washed, dried at 100° C. for 4 hours, and calcined at 550° C. for 5 hours to obtain an intermediate product.
[0154] (5) Sodium hydroxide and tetrapropylammonium hydroxide are dissolved in water and mixed to obtain a composite alkali solution, wherein the molar concentration of sodium hydroxide is 0.36 mol / L, and the molar concentration of tetrapropylammonium hydroxide is 0.46 mol / L. The intermediate product is placed in the composite alkali solution, wherein the mass ratio of the intermediate product to the composite alkali solution is 1:4.2, and a desiliconization-recrystallization reaction is carried out in a hydrothermal reactor at 170°C for 32 hours. After the reaction, the product is cooled, separated, washed, dried at 100°C for 4 hours, and calcined at 550°C for 5 hours to obtain a 3D printed molecular sieve catalyst.
[0155] Example 3
[0156] (1) Preparation of aluminosilicate ceramic green body:
[0157] (1-1) Using diatomite as a silicon-based powder and metakaolin as an auxiliary powder, the silicon-based powder mass fraction is 65% (on a dry basis) and the auxiliary powder mass fraction is 35% (on a dry basis) to obtain aluminosilicate, wherein the D90 particle size of the aluminosilicate is 10 μm;
[0158] (1-2) 2,4,6-trimethylbenzoyl-diphenylphosphine oxide (TPO) is used as a photoinitiator, polyurethane acrylate prepolymer is used as a prepolymer, and 1,6-hexanediol diacrylate (HDDA) is used as a monomer, and the mixture is mixed according to the ratio of 4% of the photoinitiator, 35% of the prepolymer, and 61% of the monomer to obtain a photosensitive resin;
[0159] (1-3) mixing aluminosilicate and photosensitive resin in a mass ratio of 0.65:1, and fully ball milling in a ball mill for 14 hours (rotation speed 280 rpm) to obtain aluminosilicate photosensitive resin slurry;
[0160] (1-4) Perform 3D structure design, import the 3D model file into the 3D printing device, perform 3D printing according to the 3D model of Example 1, pour the aluminosilicate photosensitive resin slurry into the DLP light-curing printer material tank for printing, and the printing parameters are: exposure power 1mW / cm 2 , exposure time 10s (first layer exposure time 20s); after printing, the obtained aluminosilicate ceramic body is placed in anhydrous ethanol for thorough cleaning.
[0161] (2) The formed aluminosilicate ceramic body is dried, pyrolyzed and sintered. The specific pyrolysis and sintering conditions are: heating from room temperature to 450°C at a heating rate of 0.5°C / min and maintaining for 8 hours; heating from 450°C to 1200°C at a heating rate of 3°C / min and maintaining for 15 hours to obtain an aluminosilicate ceramic carrier.
[0162] (3) Using silica sol (40wt% SiO2, Qingdao Junqiang New Materials Co., Ltd.) and aluminum sulfate (99wt%, Innochem) as the silicon source and aluminum source, respectively, and tetrapropylammonium hydroxide (TPAOH, 25wt%, Innochem) as the template, the silicon source, aluminum source, template and potassium hydroxide are added into water and mixed to obtain a crystallization mother solution, wherein the molar ratio of each raw material, i.e., SiO2:Al2O3:template:X2O:H2O, is 1:0.024:0.24:0.29:86. The above mixture is crystallized at 175°C for 4 hours to obtain a crystallization incubation solution.
[0163] (4) placing the aluminosilicate ceramic carrier in a crystallization incubation solution, wherein the mass ratio of the carrier to the crystallization incubation solution is 1:9.5, and hydrothermally crystallizing the mixture of the carrier and the crystallization incubation solution at 175° C. for 30 hours. After the hydrothermal crystallization is completed, the hydrothermal crystallization product is cooled, separated, washed, dried at 100° C. for 4 hours, and calcined at 550° C. for 5 hours to obtain an intermediate product.
[0164] (5) Potassium hydroxide and tetrapropylammonium hydroxide are dissolved in water and mixed to obtain a composite alkali solution, wherein the molar concentration of potassium hydroxide is 0.44 mol / L, and the molar concentration of tetrapropylammonium hydroxide is 0.53 mol / L. The intermediate product is placed in the composite alkali solution, wherein the mass ratio of the intermediate product to the composite alkali solution is 1:6.7, and a desiliconization-recrystallization reaction is carried out in a 175°C hydrothermal reactor for 35 hours. After the reaction, the product is cooled, separated, washed, dried at 100°C for 4 hours, and calcined at 550°C for 5 hours to obtain a 3D printed molecular sieve catalyst.
[0165] Example 4
[0166] A core-shell structured 3D printed molecular sieve catalyst was prepared according to the method of Example 1, except that in step (3), the raw materials in the crystallization mother liquor were mixed in a molar ratio of SiO2:Al2O3:template:X2O:H2O=1:0.018:0.18:0.23:65 to prepare a 3D printed molecular sieve catalyst sample.
[0167] Example 5
[0168] A 3D printed molecular sieve catalyst was prepared according to the method of Example 1, except that in step (5), the molar concentration of the alkali metal in the composite alkali solution was 0.49 mol / L, and the molar concentration of the microporous template agent was 0.59 mol / L, thereby obtaining a 3D printed molecular sieve catalyst sample.
[0169] Example 6
[0170] A 3D printed molecular sieve catalyst was prepared according to the method of Example 1, except that in step (5), the mass ratio of the intermediate product to the composite alkali solution was 1:3.5, and a 3D printed molecular sieve catalyst sample was prepared.
[0171] Comparative Example 1
[0172] A 3D printed molecular sieve catalyst was prepared according to the method of Example 1, except that no alkali metal hydroxide was added to the composite alkali solution in step (5), and a 3D printed molecular sieve catalyst sample was prepared.
[0173] The SEM image of the sample of Comparative Example 1 is as follows: Fig. 9 As shown, from Fig. 9 It can be seen that due to the lack of addition of alkali metal hydroxide, the core phase ZSM-5 molecular sieve did not undergo subsequent desiliconization-recrystallization reaction, so the core-shell structure was not formed on the surface of the 3D printed carrier, and only the core phase ZSM-5 molecular sieve was distributed on the outer surface of the 3D printed catalyst.
[0174] Comparative Example 2
[0175] The 3D printed molecular sieve catalyst was prepared according to the method of Example 1, except that no microporous template agent was added to the composite alkali solution in step (5), and the 3D printed molecular sieve catalyst sample was prepared. The SEM image of the sample of Comparative Example 2 is as follows: Fig.10 As shown, from Fig.10 It can be seen that since no microporous template agent was added to the composite alkali solution, only subsequent desiliconization reaction occurred on the surface of the core phase ZSM-5 molecular sieve but no recrystallization reaction occurred. Therefore, no core-shell structure was formed on the surface of the 3D printed carrier, and only the core phase ZSM-5 molecular sieve was distributed on the outer surface of the 3D printed catalyst.
[0176] Comparative Example 3
[0177] The hydrogenated ZSM-5 powder was tableted to prepare 40-60 mesh molecular sieve particles, the hydrogenated ZSM-5 powder was 35% commercial hydrogenated molecular sieve + 65% quartz sand by weight, and was directly used for the evaluation of alkane molecule catalytic cracking. Except for the different catalysts, other reaction evaluation conditions were the same as in Example 1.
[0178] Test Example 1
[0179] The mass percentage of ZSM-5 molecular sieve, the average particle size of micron particles, the silicon-aluminum atomic ratio of the core phase molecular sieve, the average particle size of the nanoparticles, the silicon-aluminum atomic ratio of the shell molecular sieve, the shell thickness, and the micropore volume and mesopore volume of the 3D printed molecular sieve catalysts prepared in the embodiments and comparative examples are shown in Table 1.
[0180] Table 1 Properties of the molecular sieve catalyst samples prepared in Examples and Comparative Examples
[0181]
[0182]
[0183] As can be seen from Table 1, the shell nano ZSM-5 molecular sieve of the 3D printed molecular sieve catalyst prepared in the embodiment has a high silicon-aluminum ratio, and the core phase ZSM-5 molecular sieve has a low silicon-aluminum ratio. This structure and composition are beneficial to reducing the side reactions on the outer surface of the molecular sieve, increasing the mesopore volume, shortening the reactant transmission path, and optimizing the product distribution.
[0184] Test Example 2
[0185] Catalytic activity test of core-shell structured 3D printed molecular sieve catalyst.
[0186] First, the prepared 3D printed molecular sieve catalyst was placed in a 0.1 g / mL ammonium sulfate aqueous solution (catalyst: ammonium sulfate mass ratio = 2:1), stirred at 80°C for 2 hours for ion exchange, and exchanged twice in total to obtain an ammonia-type catalyst. The ammonia-type catalyst was then washed, dried, and calcined at 550°C for 4 hours to obtain a hydrogen-type catalyst for catalytic cracking experiments.
[0187] The pretreated 3D printed molecular sieve catalyst was placed in a fixed bed reactor with a reaction pressure of 0.95 MPa, reaction temperatures of 500 °C and 550 °C, and a feed weight hourly space velocity (WHSV) of 8 h -1 ; The catalyst-to-oil ratio is 3 (mass ratio of catalyst amount to total feed). After the reaction, the liquid phase material is collected by cold bath, and the gas phase product is collected by drainage gas collection method. The liquid phase product is analyzed by Agilent 7890B (HP-PONA column) chromatography, and the gas phase product is analyzed by Agilent 6890 chromatography.
[0188] The n-octane conversion rate is calculated according to the following formula: n-octane conversion rate = 1-(n-octane mass in liquid product / n-octane raw material mass) × 100%;
[0189] Propylene selectivity = propylene yield / n-octane conversion, propylene yield = propylene output / n-octane raw material mass × 100%, the results are shown in Table 2.
[0190] Table 2 Conversion rate of samples obtained from various examples and comparative examples in catalytic cracking reaction of n-octane
[0191]
[0192] As can be seen from Table 2, the 3D printed molecular sieve catalysts prepared in Examples 1-6 were used for catalytic cracking reactions, and the conversion rates were significantly higher than those in Comparative Examples 1-2 under the same reaction conditions, and had a better cracking effect on hydrocarbon molecules.
[0193] When the catalyst of Comparative Example 3 was used for catalytic cracking reaction, the conversion rate was also significantly lower than that of the embodiment under the same reaction conditions.
[0194] Compared with traditional molecular sieve powder, the 3D printed ZSM-5 molecular sieve catalyst prepared by the present invention is easy to separate and recover from the synthetic solution, the synthesis process has low equipment requirements, and has high catalytic activity. Therefore, the present invention has a good application prospect.
[0195] The preferred embodiments of the present invention are described in detail above, but the present invention is not limited thereto. Within the technical concept of the present invention, the technical solution of the present invention can be subjected to a variety of simple modifications, including the combination of various technical features in any other suitable manner, and these simple modifications and combinations should also be regarded as the contents disclosed by the present invention and belong to the protection scope of the present invention.
Claims
1. A 3D printed molecular sieve catalyst, characterized in that: The catalyst comprises a carrier and a ZSM-5 molecular sieve having a core-shell structure, wherein the mass percentage of the ZSM-5 molecular sieve in the catalyst is 20-45%; The ZSM-5 molecular sieve comprises a core phase ZSM-5 molecular sieve and a shell ZSM-5 molecular sieve, wherein the core phase ZSM-5 molecular sieve is distributed on the outer surface of the carrier in the form of micron particle aggregates, and the average particle size of the micron particles is 1-5 microns; The shell ZSM-5 molecular sieve covers the outer surface of the core phase ZSM-5 molecular sieve in the form of nanoparticles, and the average particle size of the nanoparticles is 50-300nm; the average thickness of the coating layer formed by the shell ZSM-5 molecular sieve is 50-400nm.
2. The catalyst according to claim 1, wherein The mass percentage of ZSM-5 molecular sieve in the catalyst is 30-43%; Preferably, the carrier has a multi-porous self-supporting three-dimensional structure, and more preferably a self-supporting three-dimensional structure having parallel radial and axial interconnected pore structures; Preferably, in the core phase ZSM-5 molecular sieve, the average particle size of the micron particles is 1.5-4.5 microns; Preferably, in the shell ZSM-5 molecular sieve, the average particle size of the nanoparticles is 70-280 nm; Preferably, the average thickness of the coating layer formed by the shell ZSM-5 molecular sieve is 100-300 nm.
3. The catalyst according to claim 1 or 2, wherein The silicon-aluminum atomic molar ratio of the core phase ZSM-5 molecular sieve is 10-25, preferably 12-23; Preferably, the molar ratio of silicon to aluminum atoms in the shell ZSM-5 molecular sieve is 30-100, preferably 40-85; Preferably, the catalyst has micropores and mesopores; Preferably, the micropore volume of the catalyst is 0.03-0.08 cm 3 / g, preferably 0.04-0.07cm 3 / g; Preferably, the mesopore volume of the catalyst is 0.08-0.15 cm 3 / g, preferably 0.1-0.13cm 3 / g.
4. A method for preparing a 3D printed molecular sieve catalyst, characterized in that: The method comprises the following steps: (1) providing an aluminosilicate photosensitive resin slurry containing aluminosilicate and a photosensitive resin, and then performing 3D printing to obtain an aluminosilicate ceramic body; (2) sintering the aluminosilicate ceramic body to obtain an aluminosilicate ceramic carrier; (3) crystallizing a crystallization mother solution containing a silicon source, an aluminum source, a template, an alkali source and water to obtain a crystallization incubation solution; (4) hydrothermally crystallizing the aluminosilicate ceramic carrier in a crystallization incubation solution, and then calcining a solid product obtained by the hydrothermal crystallization to obtain an intermediate product; (5) The intermediate product is subjected to a desiliconization-recrystallization reaction in a composite alkali solution, and a 3D printed molecular sieve catalyst is obtained after calcination.
5. The method according to claim 4, wherein: The aluminosilicate comprises silicon-based powder and auxiliary powder, wherein the mass percentage of silicon-based powder on a dry basis is 35-65%, preferably 45-60%, and the mass percentage of auxiliary powder on a dry basis is 35-65%, preferably 40-55%; Preferably, the silicon-based powder is selected from at least one of silicon dioxide, white carbon black and diatomaceous earth; Preferably, the auxiliary powder is selected from at least one of kaolin, metakaolin, bentonite and montmorillonite.
6. The method according to claim 4 or 5, wherein: The mass ratio of the aluminosilicate to the photosensitive resin is 0.5-1:1, preferably 0.6-0.9:1; Preferably, the raw materials of the photosensitive resin include 1-5% of photoinitiator, 30-65% of prepolymer, and 30-65% of monomer by mass percentage, preferably include 1.5-4% of photoinitiator, 35-60% of prepolymer, and 37-62% of monomer by mass percentage; Preferably, the photoinitiator is selected from at least one of 2,4,6-trimethylbenzoyl-diphenylphosphine oxide, phenylbis(2,4,6-trimethylbenzoyl)phosphine oxide and isopropylthioxanthone; Preferably, the prepolymer is an epoxy acrylate prepolymer and / or a polyurethane acrylate prepolymer; Preferably, the monomer is selected from at least one of 1,6-hexanediol diacrylate, tripropylene glycol diacrylate and trimethylolpropane triacrylate.
7. The method according to any one of claims 4 to 6, wherein: The conditions for 3D printing include: the light curing exposure power is 0.5-5mW / cm 2 , the exposure time of the first layer is 15-30s, the exposure time of other layers is 5-15s, and the thickness of a single layer of light curing is 20-100μm; Preferably, the aluminosilicate ceramic carrier has a multi-porous self-supporting three-dimensional structure, and more preferably has a self-supporting three-dimensional structure with parallel radial and axial interconnected pores.
8. The method according to any one of claims 4 to 7, wherein: The sintering conditions in step (2) include: a temperature of 1100-1300° C. and a time of 5-20 hours; Preferably, the method further comprises pyrolyzing the aluminosilicate ceramic body before sintering, and the pyrolysis conditions include: temperature of 350-550° C. and time of 5-15 hours.
9. The method according to any one of claims 4 to 8, wherein: In the crystallization mother solution, the aluminum source is calculated as Al2O3, the silicon source is calculated as SiO2, and the alkali source is calculated as X2O, and the molar ratio of SiO2:Al2O3:template:X2O:H2O is 1:(0.018-0.027):(0.18-0.27):(0.22-0.33):(65-100), preferably 1:(0.02-0.025):(0.2-0.25):(0.24-0.31):(70-90); Preferably, the silicon source is silica sol and / or tetraethyl orthosilicate; the aluminum source is selected from at least one of aluminum sulfate, aluminum isopropoxide and aluminum trichloride; the template is an organic amine microporous template for preparing ZSM-5; Preferably, the alkali source is sodium hydroxide and / or potassium hydroxide.
10. The method according to any one of claims 4 to 9, wherein: The crystallization conditions of step (3) include: a crystallization temperature of 155-185° C., preferably 165-180° C., and a crystallization time of 3-10 h, preferably 4-9 h; Preferably, in step (4), the mass ratio of the aluminosilicate ceramic carrier to the crystallization incubation solution is 1:5-12, preferably 1:6.5-10, based on their respective total mass; Preferably, the conditions of the hydrothermal crystallization include: a crystallization temperature of 155-185°C, preferably 165-180°C, a crystallization time of 12-40h, preferably 15-35h; Preferably, the calcination conditions include: a temperature of 500-600° C. and a time of 4-8 hours.
11. The method according to any one of claims 4 to 10, wherein: In step (5), the composite alkali solution includes an alkali metal hydroxide and a microporous template agent; Preferably, the alkali metal hydroxide is sodium hydroxide and / or potassium hydroxide; the microporous template is tetrapropylammonium hydroxide and / or tetrapropylammonium bromide; Preferably, the molar concentration of the alkali metal in the composite alkali solution is 0.3-0.5 mol / L, preferably 0.34-0.46 mol / L; the molar concentration of the microporous template is 0.4-0.6 mol / L, preferably 0.44-0.56 mol / L.
12. The method according to any one of claims 4 to 11, wherein: In step (5), the mass ratio of the intermediate product to the composite alkali solution is 1:3-8, preferably 1:4-7, based on their respective total mass; Preferably, the desiliconization-recrystallization conditions include: reaction temperature of 155-185°C, preferably 165-180°C, reaction time of 15-50h, preferably 20-40h; Preferably, in step (5), the calcination conditions include: temperature of 500-600° C. and time of 4-8 h.
13. A 3D printed molecular sieve catalyst prepared by the preparation method according to any one of claims 4 to 12.
14. Use of the 3D printed molecular sieve catalyst according to any one of claims 1-3 and 13 in catalytic cracking reactions.
Citation Information
Patent Citations
ZSM-5 / ZSM-5 core-shell type zeolite molecular sieve
CN101723401A
Core-shell type MFI / MFI molecular sieve and preparation method thereof
CN112705248A
Catalytic cracking catalyst for producing high-yield low-carbon olefins through hydrogenation of LCO as well as preparation method and application of catalytic cracking catalyst
CN114130426A
Application of core-shell molecular sieve in heavy oil catalytic cracking catalyst
CN114425418A
Water-based 3D printing light-cured slurry, light-cured product and preparation method of light-cured product
CN115991592A